Proceedings of the Thirty-First International Joint Conference on Artificial Intelligence 2022
DOI: 10.24963/ijcai.2022/769
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Efficient Training of Large Neural Networks

Abstract: Pretrained models have produced great success in both Computer Vision (CV) and Natural Language Processing (NLP). This progress leads to learning joint representations of vision and language pretraining by feeding visual and linguistic contents into a multi-layer transformer, Visual-Language Pretrained Models (VLPMs). In this paper, we present an overview of the major advances achieved in VLPMs for producing joint representations of vision and language. As the preliminaries, we briefly describe the general tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Since understanding these differences is crucial for identifying future challenges and opportunities, it was important to cross-check findings with previous papers. Therefore, it can be concluded that the findings from this paper are in line with [58,59], where it was previously discovered that companies with well-established AI strategies are likely to have a competitive advantage in terms of efficient AI integration.…”
Section: Key Findings and Insightssupporting
confidence: 77%
“…Since understanding these differences is crucial for identifying future challenges and opportunities, it was important to cross-check findings with previous papers. Therefore, it can be concluded that the findings from this paper are in line with [58,59], where it was previously discovered that companies with well-established AI strategies are likely to have a competitive advantage in terms of efficient AI integration.…”
Section: Key Findings and Insightssupporting
confidence: 77%
“…These materials pose a direct risk to human health and are also reported to increase the chances of cancer later in life. The above drawbacks can be partially solved by the implementation of the so-called "green AI", which uses specially designed neural networks with lower power consumption and, consequently, lesser ecological impact [94].…”
Section: Sustainable Aimentioning
confidence: 99%
“…Such neural networks often do not fit a single GPU. To address this limitation, different approaches and strategies can be applied in order to train large neural networks effectively [81]. To deal with overfitting and to enhance model generalization, the dropout technique is usually implemented.…”
Section: Deep Learning Algorithmsmentioning
confidence: 99%